Pillared Mo2TiC2 MXene for high-power and long-life lithium and sodium-ion batteries. Issue 11 (20th April 2021) - Maughan, Philip A.; Bouscarrat, Luc; Seymour, Valerie R.; Shao, Shouqi; Haigh, Sarah J.; Dawson, Richard; Tapia-Ruiz, Nuria; Bimbo, Nuno
Abstract : We apply a silica pillaring method to create a porous Mo2 TiC2 MXene with nanoengineered interlayer distances, significantly improving performance in Li and Na-ion batteries. The charge storage mechanism is studied experimentally for the first time. Abstract : In this work, we apply an amine-assisted silica pillaring method to create the first example of a porous Mo2 TiC2 MXene with nanoengineered interlayer distances. The pillared Mo2 TiC2 has a surface area of 202 m 2 g −1, which is among the highest reported for any MXene, and has a variable gallery height between 0.7 and 3 nm. The expanded interlayer distance leads to significantly enhanced cycling performance for Li-ion storage, with superior capacity, rate capably and cycling stability in comparison to the non-pillared analogue. The pillared Mo2 TiC2 achieved a capacity over 1.7 times greater than multilayered MXene at 20 mA g −1 (≈320 mA h g −1 ) and 2.5 times higher at 1 A g −1 (≈150 mA h g −1 ). The fast-charging properties of pillared Mo2 TiC2 are further demonstrated by outstanding stability even at 1 A g −1 (under 8 min charge time), retaining 80% of the initial capacity after 500 cycles. Furthermore, we use a combination of spectroscopic techniques ( i.e. XPS, NMR and Raman) to show unambiguously that the charge storage mechanism of this MXene occurs by a conversion reaction through the formation of Li2 O. This reaction increases by 2-fold the capacity beyond intercalation, and therefore, its understanding is crucial for further development of this family of materials. In addition, we also investigate for the first time the sodium storage properties of the pillared and non-pillared Mo2 TiC2 .